Spatiotemporal differences in otoconial gene expression. Issue 12 (12th November 2016) - Xu, Yinfang; Zhang, Yan; Lundberg, Yunxia Wang
Abstract: Otoconia are minute biocrystals composed of glycoproteins, proteoglycans, and CaCO3, and are indispensable for sensory processing in the utricle and saccule. Otoconia abnormalities and degeneration can cause or facilitate crystal dislocation to the ampulla, leading to vertigo and imbalance in humans. In order to better understand the molecular mechanism controlling otoconia formation and maintenance, we have examined the spatial and temporal expression differences of otoconial genes in the mouse inner ear at developmental, mature and aging stages using whole transcriptome sequencing (RNA‐Seq) and quantitative RT‐PCR. We show that the expression levels of most otoconial genes are much higher in the utricle and saccule compared with other inner ear tissues before postnatal stages in C57Bl/6J mice, and the expression of a few of these genes is restricted to the embryonic utricle and saccule. After the early postnatal stages, expression of all otoconial genes in the utricle and saccule is drastically reduced, while a few genes gain expression dominance in the aging ampulla, indicating a potential for ectopic debris formation in the latter tissue at old ages. The data suggest that the expression of otoconial genes is tightly regulated spatially and temporally during developmental stages and can become unregulated at aging stages. Birth Defects Research (Part A) 106:613–625, 2016. © 2016 Wiley Periodicals, Inc.